2011
DOI: 10.1007/s12571-010-0102-3
|View full text |Cite
|
Sign up to set email alerts
|

A strategic framework for improving food security in Arab countries

Abstract: In 2007 and the first half of 2008, a sharp rise in agricultural commodity and food prices triggered grave concerns about food security, malnutrition and increased poverty. While the threat of a prolonged food-price shock receded in the second half of 2008, many factors underlying the price volatility are likely to persist, and will require careful management if future food-price shocks are to be avoided. This paper suggests three strategies that, together, could reduce vulnerability to price shocks: (1) stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…Khouri et al (2011) reviewed lessons learnt from this price crisis for the MENA and discuss several policy options. Lampietti et al (2011) suggested three strategies that would be feasible and effective in the MENA for reducing the region's vulnerability to price shocks which are the extension of domestic safety nets, the increase of domestic food production and the reduction of consumers' exposure to food price volatility.…”
Section: Introductionmentioning
confidence: 99%
“…Khouri et al (2011) reviewed lessons learnt from this price crisis for the MENA and discuss several policy options. Lampietti et al (2011) suggested three strategies that would be feasible and effective in the MENA for reducing the region's vulnerability to price shocks which are the extension of domestic safety nets, the increase of domestic food production and the reduction of consumers' exposure to food price volatility.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many of these publications shed light on the Arab/MENA/ Western Asia situation, in general (Breisinger et al, 2011(Breisinger et al, , 2010ESCWA, 2010;Harrigan, 2014;Lampietti et al, 2009), while including some commentary on the situation in the Gulf States, in particular. These publications tend to describe the situation from the economic perspective, reflecting on issues such as global trade, poverty levels, and job creation.…”
Section: Introductionmentioning
confidence: 99%
“…In MENA, the interventions come in many forms, but consumer subsidies are the most favored instrument (Lampietti et al 2011 At the same time, the capacity of governments to shore up safety net programs against high food prices differs among countries in the region (World Bank 2009, 2011b. All else equal, countries with large fiscal deficits and high cereal import dependency are least able to absorb a wheat price shock.…”
Section: Introductionmentioning
confidence: 99%